Obrazy dziecięcej zabawy (z) muzyką w wypowiedziach pokolenia pięćdziesięciolatków – kontekst kulturowy i pedagogiczny muzycznej zabawy - Ewa Szatan (Problemy Wczesnej Edukacji)
Musical play is one of the forms of children’s activity. You can indicate its values, define goals and functions. It is a type of activity that a child undertakes voluntarily. In history, the approach of adults to children’s play has been different, but in the last century it has been noticed that through play / play, it is easier for a younger child to learn about the world and reality, and the knowledge thus acquired is more permanent. I was interested in what images of children’s musical games was remembered by adults from the 50-year-old generation who lived their childhood in conditions other than modern children. The text is an attempt to describe their experiences and place them in a pedagogical and cultural context.